Comparison of Hemorrhoidectomy by Ligasure and Conventional Milligan Morgans Technique - Akhtar, Fahad; Waqar, S. H.; Noor, Aiman; Jamal, Zakir (Indus Journal of Bioscience Research, 2025)
Objective: To compare the outcomes of LigaSure versus the conventional Milligan-Morgan technique in patients undergoing hemorrhoidectomy. Study Settings: Department of General Surgery, Pakistan Institute of Medical Sciences (PIMS), Islamabad from 20 August 2004 to 20 February 2025. Duration of Study: Six months following approval from the institutional ethical committee. Data Collection: A randomized controlled trial was conducted on 60 patients with grade 3 or 4 hemorrhoids, divided into two groups: LigaSure (Group A) and Milligan-Morgan (Group B). Operative time, intraoperative blood loss, and postoperative pain were measured using a stopwatch, gauze count, and the 0–10 Visual Analog Scale (VAS) at 6, 12, and 24 hours postoperatively. Results: The LigaSure group exhibited significantly shorter operative times (38.26±9.42 minutes vs. 56.11±10.90 minutes, ????<0.001), lower intraoperative blood loss (53.01±20.69 mL vs. 72.35±22.99 mL, ????=0.001), and reduced postoperative pain scores across all intervals (e.g., 3.79±0.84 at 6 hours vs. 5.57±0.79, ????<0.001). These findings highlight the LigaSure technique’s efficiency, hemostatic precision, and ability to reduce postoperative pain. Conclusion: LigaSure hemorrhoidectomy demonstrated superior outcomes compared to the Milligan-Morgan technique, offering reduced operative time, intraoperative blood loss, and postoperative pain. It provides a safer and more efficient alternative for hemorrhoid surgery, potentially reducing hospital burden and improving patient recovery.